2001
DOI: 10.1017/s0959259801112104
|View full text |Cite
|
Sign up to set email alerts
|

Care work and quality of care for older people: a review of the research literature

Abstract: Redfern (2001). Care work and quality of care for older people: a review of the research literature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
70
2
2

Year Published

2006
2006
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(76 citation statements)
references
References 45 publications
2
70
2
2
Order By: Relevance
“…Earlier studies have identified the importance of matching education programs to the needs of care staff. A review of care work and care of older people concluded that educational training programs must be relevant to staff needs if they are to have a positive impact on staff and patient outcomes (Hannan, Norman, & Redfern, 2001). To address gaps in understanding of the specific learning needs of home care providers, this study examined the frequency of specific dementia-related work activities, perceived competence in dementia-related work activities, and priorities for continuing education topics among home care nurses, case managers, and nursing aides, in a predominantly rural health region.…”
mentioning
confidence: 99%
“…Earlier studies have identified the importance of matching education programs to the needs of care staff. A review of care work and care of older people concluded that educational training programs must be relevant to staff needs if they are to have a positive impact on staff and patient outcomes (Hannan, Norman, & Redfern, 2001). To address gaps in understanding of the specific learning needs of home care providers, this study examined the frequency of specific dementia-related work activities, perceived competence in dementia-related work activities, and priorities for continuing education topics among home care nurses, case managers, and nursing aides, in a predominantly rural health region.…”
mentioning
confidence: 99%
“…There are many ways to measure it, among which Likert scales are the most commonly used. Research on work satisfaction has also been active concerning care work (see e.g., Hannan et al, 2001;Häggström et al, 2005;Redfern et al, 2002). On the based of instruments used generally in work-satisfaction research, the Nordic research team of the NORDCARE project included ten items of work satisfaction in the questionnaire with which respondents were asked to evaluate different issues of their work and working conditions using a four-point Likert scale.…”
Section: Methodsmentioning
confidence: 99%
“…In one survey, 50% of RNs in care homes rated their knowledge as insufficient in areas such as psychiatric illness, dealing with threat and violence, dementia, computer skills and healthcare and social welfare law [6]. Other research has suggested that current competencies do not correspond with the tasks required in nursing homes [7].Competency development is known to predict work satisfaction and lower turnover rates [8].Developing competencies in this workforce will facilitate professional development, more clearly define a career pathway in care home nursing and increase the status of work in this area.This study set out to develop a competency framework for RNs working in care homes using the Delphi method. …”
mentioning
confidence: 99%